Arrest As Displaced Aggression. (October 2013) - Johnson, Richard R.
Applied to police officers, displaced aggression theory would suggest that an officer primed for a negative affect by a personal family conflict will be more likely to arrest, and less likely to show lenience toward, criminal suspects engaged in minor offenses. The present study primed a sample of police officers for either positive or negative affects. The police officer participants were then presented with a vignette involving a drunken driver that contained details presenting only the minimum level of evidence to justify a legal arrest. The respondent officers primed for a negative affect were significantly more likely to indicate they would arrest the driver. This result held even after controlling for the officers' ascribed characteristics in a multivariate analysis. The results suggest that officers primed for a negative affect by personal circumstances are more likely to take out their frustration by exercising their discretion to arrest for a minor offense.